Divide And Conquer Algorithm Based an Efficient Scheme for Compression of Electro Cardiac Signal - Vienala Sapthagiri, Priyanka Konatham, Murugesan Senthil Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
An electrocardiogram (ECG) is a standard test that checks how the heart is working by measuring the electrical action of the heart. Individuals with a heart related issues have the long record of ECGs for symptomatic purposes, which brings about the necessity of a lot of storage space. Subsequently there is a requirement for a framework which includes pressure of ECG signals alongside ECG investigation. ECG pressure is a superior technique for minimize computational many-sided quality as far as storage. Flag pressure and flag examination have request in numerous application territories particularly in biomedical zone. ECG signals are diverse for every individual. ECG design acknowledgment is a standout amongst the most dependable coronary illness recognizable proof strategies. ECG is the standard tool for monitoring and diagnosing cardiovascular issues by measuring electrical movement of the heart. The cathodes connected to the body identify the electrical movement of the heart. From every terminal the ECG signals will record and store for a drawn out stretch of time.